Potential Pollution of Liquid Waste from the Agro-Industry to Rivers in the Area Around Tanjung Api-Api - AR, Hasmawaty; Yulistia , Eriyana; Renilaili (PT FORMOSA CENDEKIA GLOBAL, 2024)
Due to its high regional significance, Tanjung Api-api, currently the mainstay of South Sumatra Province, serves as a focal point for agro-industrial development programs. This research aims to identify the potential for liquid waste pollution in rivers from agro-industries around Tanjung Api-api. This research was carried out through four stages: (a) collecting physical data on land, forests, and rivers in the ecosystem conditions around the industrial area of the Tanjung Api-api area. (b) analyzing data on the physical and chemical parameters of the Telang River, (c) analyzing several physical and chemical parameters of Telang River water, (d) obtaining data on the physical and chemical parameters of liquid waste in the influent and effluent of several WWTP agro-industries in the Gasing area that have been operating. Water quality measurements were conducted in the Telang and Gasing rivers. The parameters measured and observed were TSS, pH, BOD, COD, and fatty oil parameters, respectively, once in the afternoon and evening during high and low tide, at three points: downstream, middle, and upstream. The results showed that the physical, organic, and inorganic chemical parameters in the Telang River were still below the BMLC threshold. The quantity and quality of industrial wastewater in Gasing are still below the BMLC standard for each industry but are almost close to the established quality standards. It is recommended to utilize the sludge into something more valuable, considering that the TSS produced from sludge dewatering is relatively high.